Pelatihan digitalisasi data pada Organisasi karang taruna Budi Utomo dan perangkat desa Sari Mulya Jujuhan Ilir - Riko Muhammad Suri; Sidik Praptomo (LPPI UMN AL WASHLIYAH, 2025)
Digital data processing is a strategic effort to enhance understanding and skills in utilizing information technology for data management. This activity is motivated by the need for efficiency, accuracy, and security in storing and processing data in the digital era. The training method is conducted through a combination of material delivery, hands-on practice, and intensive guidance, enabling participants to gain not only theoretical knowledge but also practical skills in using digital tools. The materials presented include the fundamentals of digitization, the use of data processing software, digital archive management, and an understanding of data security. The training participants come from various institutional or individual backgrounds who share a common need: transitioning from manual systems to digital systems. The results of the training indicate a significant improvement in participants’ understanding and skills in carrying out the data digitization process. In addition, participants are better prepared to implement digital technology within their respective work environments. Thus, this training provides a tangible contribution to improving data management quality and supports the achievement of broader digital transformation.